The effect of grouping on achievement, classroom participation and interaction of students in modern geometry at the Manuel L. Quezon (Public) High School, Manila - De Leon, Lorenzo Padua 1918- (1972)
The effects of two different methods of grouping on the achievement of students and on their participation and interaction in the classroom were compared in this study. There was a significant difference in the achievement of the students in the specific ability group from those of the general ability group. Those in the specific ability group achieved better.
Thesis (M. Ed.) -- University of the Philippines.
Keywords: Ability groupings in education; Group work in education